2014
DOI: 10.1186/1749-7922-9-50
|View full text |Cite
|
Sign up to set email alerts
|

Catastrophic hemorrhage of adrenal pheochromocytoma following thrombolysis for acute myocardial infarction: case report and literature review

Abstract: We describe here the case of a 62-year-old man with acute abdominal syndrome and severe hemorrhagic shock following successful thrombolysis for acute cardiac infarction. Emergency surgical exploration revealed extensive intraperitoneal and retroperitoneal hemorrhage resulting from the rupture of a large adrenal tumor. The diagnosis of pheochromocytoma was confirmed by histological findings. The patient died a few hours after surgery from multiorgan failure despite resuscitation attempts. This report discusses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Other reported causes include adrenal cancer, metastatic tumor (5), adrenal cyst (6), pheochromocytoma (2,3), neoplastic lesions such as myelolipoma, hemorrhagic diathesis due to coagulation disorders such as antiphospholipid syndrome (7), or use of oral anticoagulant agents, accompanying stress, sepsis, and idiopathic adrenal hemorrhage of unknown cause (1). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other reported causes include adrenal cancer, metastatic tumor (5), adrenal cyst (6), pheochromocytoma (2,3), neoplastic lesions such as myelolipoma, hemorrhagic diathesis due to coagulation disorders such as antiphospholipid syndrome (7), or use of oral anticoagulant agents, accompanying stress, sepsis, and idiopathic adrenal hemorrhage of unknown cause (1). …”
Section: Discussionmentioning
confidence: 99%
“…Thus, urinary cortisol and catecholamines were elevated. We suspected that these elevated values were due to stress and performed precautionary 131I-MIBG scintigraphy because it has been reported that adrenal hemorrhage might develop as a complication of pheochromocytoma (2,3). However, no clear uptake was observed in the adrenal gland, and re-testing performed approximately two months later revealed that all of the adrenal hormones had normalized (data not shown).…”
Section: Case Reportmentioning
confidence: 99%
“…1 Rupture of a pheochromocytoma and the resulting retroperitoneal hemorrhage are rare complications that could transform to an abdominal catastrophe and if unrecognized and treated can rapidly lead to death. [2][3][4] There are only few published case reports of ruptured pheochromocytomas, 2 the majorities were spontaneous ruptured adrenal pheochromocytomas, the usual symptoms at presentation were acute abdomen in 77 per cent, shock in 57 per cent, lumbar pain in 25 per cent, and chest pain in 15 per cent of cases. 3 Rare cases of ruptured posttraumatic pheochromocytomas are reported.…”
Section: Traumatic Rupture Of Extra-adrenal Pheochromocytomamentioning
confidence: 99%
“…[2][3][4] There are only few published case reports of ruptured pheochromocytomas, 2 the majorities were spontaneous ruptured adrenal pheochromocytomas, the usual symptoms at presentation were acute abdomen in 77 per cent, shock in 57 per cent, lumbar pain in 25 per cent, and chest pain in 15 per cent of cases. 3 Rare cases of ruptured posttraumatic pheochromocytomas are reported. Huyghe et al 2 reported a case of lethal posttraumatic rupture of a left adrenal pheochromocytoma in which the diagnosis was only made at autopsy concluding that pheochromocytoma should be considered in cases of blunt abdominal trauma associated with unstable blood pressure, peripheral vasoconstriction, and retroperitoneal hematoma.…”
Section: Traumatic Rupture Of Extra-adrenal Pheochromocytomamentioning
confidence: 99%
See 1 more Smart Citation